2022
DOI: 10.1088/1755-1315/1118/1/012050
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic pollution in the surface water of Lake Singkarak, Indonesia

Abstract: Microplastic pollution is already at an “alarming” level in Indonesia’s marine and freshwater ecosystems. However, to the best of our knowledge, no study has reported the microplastic occurrence in the lake ecosystem in Indonesia. Lake Singkarak, a big tectonic lake, has been considered one of the priority lakes to be restored. The lake receives a high influx of plastic waste from rivers and catchment runoff. Controlling the outflow through the hydropower dam and the sluice in the main lake outlet may prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
1
2
0
1
Order By: Relevance
“…Figure 4 shows examples of microscope images of microplastics in this study. Throughout the sampling process at various locations, the predominant type of microplastics observed was film-shaped particles, which is consistent with previous findings in Surabaya River, rivers in Greater Semarang, and Singkarak Lake (Lestari et al, 2020; Andarani et al, 2023; Henny et al, 2022). Similarities between the film particles found in this study and debris from aged plastic packaging further support the notion that these particles originate from the degradation of plastic bags and packaging materials (Mohamed Nor and Obbard, 2014).…”
Section: Microplastics Characteristics In Banger Riversupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 4 shows examples of microscope images of microplastics in this study. Throughout the sampling process at various locations, the predominant type of microplastics observed was film-shaped particles, which is consistent with previous findings in Surabaya River, rivers in Greater Semarang, and Singkarak Lake (Lestari et al, 2020; Andarani et al, 2023; Henny et al, 2022). Similarities between the film particles found in this study and debris from aged plastic packaging further support the notion that these particles originate from the degradation of plastic bags and packaging materials (Mohamed Nor and Obbard, 2014).…”
Section: Microplastics Characteristics In Banger Riversupporting
confidence: 90%
“…Compared to other studies, the microplastic abundances observed in this research were relatively low. For instance, the Jeneberang River exhibited higher microplastic abundance, ranging from 5.77 ± 1.25 to 3.93 ± 1.32 particles/L (Wicaksono et al, 2021), while Lake Singkarak recorded 9.23 ± 2.14 items/m 3 (Henny et al, 2022).…”
Section: Microplastic Abundancesmentioning
confidence: 99%
“…Kye et al ( 2023) consideraron que el desarrollo urbano, tamaño y morfología del cuerpo de agua, así como la hidrodinámica local inciden en la abundancia y distribución de MP, lo que coincide con los altos niveles observados en la zona de muestreo norte, donde existe una concentración importante de infraestructura dedicada al turismo. También se ha asociado a las actividades agrícolas y conductas de turistas con la contaminación por MP en lagos (Henny et al, 2022). Posiblemente los vientos están asociados a la dispersión espacial y abundancia de MP al centro y al este del lago de Coatepeque en el mes de enero (Figura 1), aunque su origen no se pudo documentar.…”
Section: Resultados Y Discusiónunclassified
“…The presence of MPs was initially observed in coastal waters of North America during the 1970s (Carpenter et al, 1972). Nonetheless, the presence of MP pollution remains a substantial worldwide issue, with their detection reported in various aquatic settings such as oceans, rivers, lakes, estuaries, reservoirs, and even in harsh environments like Antarctica and the Arctic Ocean (Bellasi et al, 2020;Cunningham et al, 2022;Henny et al, 2022;Villegas et al, 2021). The durability, accumulation, and harmful effects on aquatic organisms make MPs an increasingly concerning environmental issue (Wardrop et al, 2016).…”
Section: Introductionmentioning
confidence: 99%